Interplay of the Wzx translocase and the corresponding polymerase and chain length regulator proteins in the translocation and periplasmic assembly of lipopolysaccharide o antigen - Marolda, Cristina L; Tatar, Laura D; Alaimo, Cristina; Aebi, Markus; Valvano, Miguel A (Journal of bacteriology, 2006)
Genetic evidence suggests that a family of bacterial and eukaryotic integral membrane proteins (referred to as Wzx and Rft1, respectively) mediates the transbilayer movement of isoprenoid lipid-linked glycans. Recent work in our laboratory has shown that Wzx proteins involved in O-antigen lipopolysaccharide (LPS) assembly have relaxed specificity for the carbohydrate structure of the O-antigen subunit. Furthermore, the proximal sugar bound to the isoprenoid lipid carrier, undecaprenyl-phosphate (Und-P), is the minimal structure required for translocation. In Escherichia coli K-12, N-acetylglucosamine (GlcNAc) is the proximal sugar of the O16 and enterobacterial common antigen (ECA) subunits. Both O16 and ECA systems have their respective translocases, WzxO16 and WzxE, and also corresponding polymerases (WzyO16 and WzyE) and O-antigen chain-length regulators (WzzO16 and WzzE), respectively. In this study, we show that the E. coli wzxE gene can fully complement a wzxO16 translocase deletion mutant only if the majority of the ECA gene cluster is deleted. In addition, we demonstrate that introduction of plasmids expressing either the WzyE polymerase or the WzzE chain-length regulator proteins drastically reduces the O16 LPS-complementing activity of WzxE. We also show that this property is not unique to WzxE, since WzxO16 and WzxO7 can cross-complement translocase defects in the O16 and O7 antigen clusters only in the absence of their corresponding Wzz and Wzy proteins. These genetic data are consistent with the notion that the translocation of O-antigen and ECA subunits across the plasma membrane and the subsequent assembly of periplasmic O-antigen and ECA Und-PP-linked polymers depend on interactions among Wzx, Wzz, and Wzy, which presumably form a multiprotein complex.